Relación de la dieta y los niveles séricos de ácido úrico en la población adulta de la junta vecinal Las Lomas de Huanchaco - diciembre 2015 - Mendoza Padilla, María Gisella (2016)
In this research, the relationship between diet and uric acid levels in adult residents of the neighborhood Las Lomas de Huanchaco was determined, using the kind of simple, prospective and cross-sectional descriptive research; with sample size of 60 adult people of both sexes who participated voluntarily. For this specific enzymatic method for the quantitative determination of uric acid in serum we were used. Coming to get that diet influences the serum uric acid levels of the adult population of the neighborhood council of the hills of Huanchaco; specifically the consumption of red meat, seafood among other conditions can increase those levels.